Strength and damage tolerance of composite–composite joints with steel and titanium through the thickness reinforcements. (September 2016) - Stelzer, S.; Ucsnik, S.; Pinter, G.
Abstract: Today's aeronautic, automotive and marine industry is in demand of structurally efficient, low weight alternatives for composite–composite joints which combine the advantages of low weight input of adhesively bonded joints and high damage tolerance of through the thickness bolted joints. In the present work, composite–composite joints are reinforced through the thickness by thin metal inserts carrying cold metal transfer welded pins (CMT pins). The influence of pin alignment and type of pin on the damage tolerance of single lap shear (SLS) composite–composite joints is investigated. The use of titanium reinforcements is evaluated and compared to stainless steel reinforced, adhesively bonded and co-cured specimens. A detailed analysis of the stress–strain behavior is given and the stiffness and energy absorption of the SLS joints during tensile loading is assessed. The results show that joints reinforced with CMT pins absorb significantly higher amounts of energy, when compared to adhesively bonded and co-cured joints.